IMPACT OF RESISTANCE IN DIMINUTION OF INFECTION AND QUANTITATIVE LOSSES CAUSED BY KARNAL BUNT (NEOVOSSIA INDICA) IN BREAD WHEAT (TRITICUM AESTIVUM L.) - SWATI; PRASHANT GOEL; RAJIV SHARMA; KANAK SRIVASTAVA (The Bioscan, 2012)
Reaction of Neovossia indica in bread wheat, with particular reference to the role of resistance in minimizing its infection and quantitative loss caused by it, were observed with virulent isolate of Neovossia indica in a set of population. Whole set of population consisted of resistant parents (HD 29, Lok 1 and Raj 3777), susceptible parents (WL 711, UP 262 and UP 2425), F1, F2 and backcross (BC1 and BC2) generations. F1 was derived from crossing between resistant and susceptible parents in half diallel fashion. Maximum percent infection i.e., 17.9% was recorded in the susceptible parent i.e, WL 711, which resulted in 4.65 % (maximum) grain yield loss, while only 0.86 % (minimum) infection resulted in 0.22% grain yield loss was recorded in the back cross generation of the cross Raj 3777/ Lok-1 (resistant x resistant). However, overall 6.0 % percent infection and grain yield loss 1.49% was recorded by all generations. The present study reveals good scope for resistance breeding in minimizing the percent infection and ultimately yield loss due to infection of Karnal bunt